Effects of volume and nozzle area in narrow-throat spark-ignited pre-chamber combustion engines. (1st April 2022) - Hlaing, Ponnya; Echeverri Marquez, Manuel; Cenker, Emre; Im, Hong G.; Johansson, Bengt; Turner, James W.G.
Highlights: Extended lean limit and low NOx emissions were achieved by narrow-throat pre-chamber design. Pre-chambers with different volumes and nozzle areas but fixed throat diameter were studied. Not all nozzle holes discharge jets when the throat to total nozzle area is less than 1. Throat to nozzle opening area ratio significantly affects pre-chamber pressure buildup. Abstract: The pre-chamber combustion concept (PCC) concept shows promises for lean combustion to achieve improved combustion stability and engine efficiency. The KAUST narrow-throat pre-chamber design, which can readily fit into the diesel injector pocket of a heavy-duty engine, has demonstrated an increased lean limit extension compared to conventional pre-chamber designs without a distinct throat. This study examines the effect of pre-chamber volume and nozzle opening area on the PCC concept by employing five different pre-chambers with fixed throat diameter. The engine was fueled with methane, and the combustion characteristics of each pre-chamber were assessed at different operating conditions. A 1-D GT-Power pre-chamber engine model was utilized to estimate the temperature and mixture composition inside the pre-chamber and main chamber. A multi-chamber heat release analysis method was applied to determine the response of the main chamber heat release process with different pre-chamber geometries. Engine-out emissions were also measured to compare the emission performance between the different pre-chambers. It was found that an increased pre-chamber volume promoted earlier ignition in the main chamber, and the throat area was a critical limiting factor in determining the engine performance for the pre-chambers with different nozzle opening areas at a given pre-chamber volume.